2005
DOI: 10.1016/j.jsgi.2004.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of Ovine Endothelial Nitric Oxide Synthase and Expression in COS-7 Cells

Abstract: While studies of human and bovine endothelial nitric oxide synthase (eNOS) demonstrate activation by Ca(2+)/calmodulin, recent progress demonstrates that eNOS phosphorylation can alter sensitivity to intracellular free calcium ([Ca(2+)](i)). The sheep, however, is widely used as a model for cardiovascular adaptation to pregnancy and ovine uterine artery endothelial cell (UAEC) eNOS undergoes pregnancy-specific (P) enhancement of activity associated with increased Ca(2+) and protein kinase signaling in response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Indeed, previous studies have demonstrated that nicotine and its metabolic product cotinine significantly decreased eNOS mRNA and protein levels, resulting in impaired endothelial-dependent relaxations in the carotid artery rings after a 24-h treatment (Conklin et al, 2001). In addition to decreased eNOS protein levels, chronic nicotine treatment significantly attenuated eNOS phosphorylation at the site of Ser1179 that is involved in eNOS activation (Cale et al, 2005;Mount et al, 2007), suggesting a decrease in the function of the eNOS enzyme. In summary, the present study demonstrates for the first time that chronic, but not acute, nicotine treatment has direct effects on contractility of the uterine artery in pregnancy and inhibits endothelium-dependent relaxations, resulting in an enhanced vasoconstriction of the pregnant uterine artery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, previous studies have demonstrated that nicotine and its metabolic product cotinine significantly decreased eNOS mRNA and protein levels, resulting in impaired endothelial-dependent relaxations in the carotid artery rings after a 24-h treatment (Conklin et al, 2001). In addition to decreased eNOS protein levels, chronic nicotine treatment significantly attenuated eNOS phosphorylation at the site of Ser1179 that is involved in eNOS activation (Cale et al, 2005;Mount et al, 2007), suggesting a decrease in the function of the eNOS enzyme. In summary, the present study demonstrates for the first time that chronic, but not acute, nicotine treatment has direct effects on contractility of the uterine artery in pregnancy and inhibits endothelium-dependent relaxations, resulting in an enhanced vasoconstriction of the pregnant uterine artery.…”
Section: Discussionmentioning
confidence: 97%
“…eNOS protein and phosphorylation levels were determined with Western blot analysis, as described previously (Cale et al, 2005;Xiao et al, 2007). Arteries were homogenized in a lysis buffer containing 150 mM NaCl, 50 mM Tris-HCl, 10 mM EDTA, 0.1% Tween 20, 0.1% ␤-mercaptoethanol, 0.1 mM phenylmethylsulfonyl fluoride, 5 g/ml leupeptin, and 5 g/ml aprotinin, pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…QuikChange Site-Directed Mutagenesis kit (Stratagene; La Jolla, CA) was used to mutate ovine eNOS cDNA (pBK-CMV) (8) Thr497 to Asp (T497D: sense oligo 5Ј-GCG CAG GCA TCA CCA GGA AGA AGG ACT TTA AGG AAG T-3Ј), Thr 497 to Ala (T497A: sense oligo 5Ј-GCG CAG GCA TCA CCA GGA AGA AGG CCT TTA AGG AAG T-3Ј), or Ser1179 to Ala (S1179A: sense oligo 5Ј-GCC GTA TAC GTA CCC AGG CCT TTT CCC TGC AGG AG-3Ј). In addition, the double mutant (T497D/ S1179A) was generated by subjecting T497D to a second round of mutagenesis with the S1179A primers.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we previously isolated the ovine eNOS cDNA and described a COS-7 ovine eNOS cell model (8) to which we now compare UAEC phosphorylation and activation of eNOS. Use of the COS-7 eNOS model also allowed us to further determine how a phosphomimetic mutation of T497 affects phosphorylation of the other known eNOS sites and to compare its activity to eNOS with two mutations predicted to be detrimental to activity (T497D/S1179A).…”
mentioning
confidence: 99%
“…PCR primer pairs were designed from different exons of NOS3, c-Jun, or L-19 to discriminate PCR products that might arise from possible chromosomal DNA contaminants. Specifically, they were derived from the cDNA clones at the following nucleotides positioned at: 2029-2049 and 2359-2379 for rat c-jun (Sakai et al, 1989), 409-430 and 685-704 for sheep NOS3 (Cale et al, 2005) and 38-56 and 370-388 for sheep L19 (GenBank A# AY158223). The internal controls for NOS3 and L-19 were 171-190 and 561-580 of the pGL3-basic vector from Promega (Madison, WI).…”
Section: Quantitative Reverse Transcription-polymerase Chain Reactionmentioning
confidence: 99%